Cognitive scripts, anxiety and styles of coping with stress in teenagers practising sports - Basiaga-Pasternak, J. (Journal of Human Kinetics, 2018)
The aim of the study was to present the relationships between the way of perceiving oneself and the world by young athletes, the cognitive anxiety and the ways of coping with stress. The target group consisted of 222 participants (114 boys and 108 girls) aged 16-20, students of sports-profiled secondary schools. The participants specialised in both winter and summer sports, as well as in individual and team sport disciplines. The following tools were implemented: Attitudes to Intrapersonal, Interpersonal and to the World Questionnaire, Coping Inventory for Stressful Situations (CISS) and Sport Anxiety Scale. The study showed that negative perception of oneself and others increases the level of cognitive anxiety and decreases the tendencies to search for social contacts in the face of stress. With regard to the positive image of oneself and others, the opposite was observed. The above relationships refer mainly to girls who practise sports.